2011
DOI: 10.4103/0976-9668.82309
|View full text |Cite
|
Sign up to set email alerts
|

Serum malondialdehyde level: Surrogate stress marker in the Sikkimese diabetics

Abstract: Background:The pbreakdown of phospholipids lead to accumulation of malondialdehyde (MDA) that is preferred as a surrogate marker of oxidative stress in diabetics.Objective:To compare serum MDA levels along with other biochemical parameters between type 2 diabetic patients with and without complications.Materials and Methods:This cross-sectional study was carried out in the Department of Biochemistry of a tertiary care teaching hospital in Sikkim on 60 type 2 diabetics and compared with 100 non-diabetic partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…T2D and PDM subjects exhibited higher levels of the plasma lipid peroxidation marker, MDA. The rise in plasma MDA among T2D has been previously reported similar to our findings [34, 35]. Hyperglycaemia promotes ROS-mediated lipid peroxidation via nonenzymatic and autoglycation pathways [1, 7].…”
Section: Discussionsupporting
confidence: 91%
“…T2D and PDM subjects exhibited higher levels of the plasma lipid peroxidation marker, MDA. The rise in plasma MDA among T2D has been previously reported similar to our findings [34, 35]. Hyperglycaemia promotes ROS-mediated lipid peroxidation via nonenzymatic and autoglycation pathways [1, 7].…”
Section: Discussionsupporting
confidence: 91%
“…There are very few studies in the literature, which have shown the association between serum bilirubin and MDA levels with diabetic microvascular complications. [ 17 18 19 20 21 22 23 24 25 ] We hypothesized that there is a correlation between the levels of bilirubin and MDA with severity of retinopathy in patients with type 2 DM. There are no studies showing the association between DR and serum bilirubin in Indian population and only a few are available with MDA levels hence this study was undertaken.…”
Section: Introductionmentioning
confidence: 99%
“…Maitreyess (2011) and Martin-Gallan (2003) has also found that MDA serum level on T2DM with complication was higher than the no complication group [12], [13]. Bhutia (2011) and Jalees (2017) found that the MDA serum level was significantly elevated in patients with diabetes compared to those in normal subjects [14], [15]. Zavar-Reza (2014) observed significant increased MDA serum level in T2DM patients with complications [16].…”
Section: Discussionmentioning
confidence: 99%